Comparative usability evaluation of consultation order templates in a simulated primary care environment. (November 2018) - Savoy, April; Patel, Himalaya; Flanagan, Mindy E.; Daggy, Joanne K.; Russ, Alissa L.; Weiner, Michael
Abstract: Communication breakdowns in the referral process negatively impact clinical workflow and patient safety. There is a lack of evidence demonstrating the impact of published design recommendations addressing contributing issues with consultation order templates. This study translated the recommendations into a computer-based prototype and conducted a comparative usability evaluation. With a scenario-based simulation, 30 clinicians (referrers) participated in a within-group, counterbalanced experiment comparing the prototype with their present electronic order entry system. The prototype significantly increased satisfaction (Cohen's d  = 1.80, 95% CI [1.19, 2.41], p  < .001), and required significantly less mental effort ( d  = 0.67 [0.14, 1.20], p  < .001). Regarding efficiency, the prototype required significantly fewer mouse clicks (mean difference = 29 clicks, p  < .001). Although overall task time did not differ significantly ( d  = −0.05 [−0.56, 0.47]), the prototype significantly quickened identification of the appropriate specialty clinic (mean difference = 12 s, d  = 0.98 [0.43, 1.52], p  < .001). The experimental evidence demonstrated that clinician-centered interfaces significantly improved system usability during ordering of consultations. Highlights: Illustrates a useful and usable new prototype for electronic consultation orders. Applied human factors principles to translate and evaluate design recommendations. New prototype improved physician satisfaction, workload, and efficiency with orders. Results of comparative usability evaluation support translation into practice. Informs design of consultation order templates to reduce communication breakdowns.